2015
DOI: 10.3945/ajcn.115.116863
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inflammatory index and telomere length in subjects with a high cardiovascular disease risk from the PREDIMED-NAVARRA study: cross-sectional and longitudinal analyses over 5 y

Abstract: This study showed both cross-sectional and longitudinal associations between the inflammatory potential of the diet and telomere shortening in subjects with a high cardiovascular disease risk. Our findings are consistent with, but do not show, a beneficial effect of adherence to an anti-inflammatory diet on aging and health by slowing down telomere shortening. These results suggest that diet might play a key role as a determinant of TL through proinflammatory or anti-inflammatory mechanisms. This trial was reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
107
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 117 publications
(112 citation statements)
references
References 53 publications
3
107
0
2
Order By: Relevance
“…Adherence to healthy dietary pattern like Mediterranean diet was also protective in this case-control study 37 . A diet with a high Mediterranean diet score (MDS), as defined by Trichopoulou et al 2003 38 , would also have a low DII (or E-DII) score as we have observed previously in other Mediterranean populations 3941 . In this study, we observed an inverse Spearman correlation of −0.43 (p-value <0.0001).…”
Section: Discussionmentioning
confidence: 51%
“…Adherence to healthy dietary pattern like Mediterranean diet was also protective in this case-control study 37 . A diet with a high Mediterranean diet score (MDS), as defined by Trichopoulou et al 2003 38 , would also have a low DII (or E-DII) score as we have observed previously in other Mediterranean populations 3941 . In this study, we observed an inverse Spearman correlation of −0.43 (p-value <0.0001).…”
Section: Discussionmentioning
confidence: 51%
“…Cabe señalar que solo tres de los estudios con resultados significativos en relación con la asociación entre los patrones dietéticos y TL evaluaron la calidad de la dieta (147,156,164).…”
Section: Resultados Y Discusiónunclassified
“…Further corroboration of the validation of the DII is that fact that it has been associated with a wide range of outcomes associated with inflammation. The DII was previously associated with several types of cancer (e.g., colorectal, prostate, pancreas, lung, esophageal) (612), cardiovascular disease (13), components of metabolic syndrome (5), telomere length (14), obesity (15), asthma (16), and mortality (17, 18). However, previous construct validation studies using inflammatory markers were mainly conducted among populations that were mainly European Americans.…”
Section: Introductionmentioning
confidence: 99%